Translation between Faithfulness and Distorsion - Kaddouri, Souad (الأكاديمية الليبية للدراسات العليا / مدرسة اللغات, 2025)
في عصر العولمة، تُعتبر الترجمة أداة مؤثرة ومقنعة، لا سيما للآداب الوطنية التي تهدف إلى تجاوز الحدود الجغرافية والثقافية، والأدب العربي بترجماته إلى اللغات العالمية ليس استثناءً. تسعى هذه الورقة إلى دراسة العلاقة بين العولمة والترجمة، بالإضافة إلى استكشاف تأثير العولمة على نقل الأدب العربي إلى لغات أخرى من حيث محتواه وأسلوبه واستقباله. وعلى الرغم من تزايد عدد الترجمات، لا يزال تحدي تمثيل الأدب العربي في اللغات الأجنبية يطرح عدة تساؤلات؛ كيف تؤثر الديناميكيات الثقافية والسياسية للعولمة على اختيار الأعمال المراد ترجمتها؟ هل هناك معايير إلزامية لتلبية التفضيلات العالمية؟ إلى أي مدى تحافظ الترجمة بشكل أصيل على هوية الواقع الاجتماعي العربي، وخاصة الأعمال المتعلقة بالمرأة والدين والصراعات الأهلية؟ ومن ثم، تستخدم الدراسة نظرية ما بعد الاستعمار ونظرية الترجمة الثقافية كإطارين لدراسة الديناميكيات المختلفة التي تتحكم في عملية الترجمة في أعمال أدبية مختارة. يكشف البحث أن الترجمة قد تجرد النص من خلفيته الثقافية وتفاصيله اللغوية الدقيقة بهدف تدويل تفسيره. لذا، يؤكد هذا البحث أن الترجمة في ظل العولمة الراهنة سلاح ذو حدين؛ إذ قد تكون أداة لتعزيز التفاهم الوطني العالمي، أو أداة لنشر مفاهيم متحيزة. لذا، تقترح الدراسة أن على المترجمين العرب القيام بدور أكثر فاعلية في تحديد الأعمال المراد ترجمتها وكيفية نقلها إلى لغات أخرى Abstract In the era of globalization, translation is regarded as an influential and persuasive instrument, mainly for national literatures that aim to transcend geographical and cultural boundaries and Arabic literature with its translations into international languages is no exception. This paper seeks to examine the association between globalization and translation, as well as to explore the influence of globalization on the transmission of Arabic literature into other languages vis-à-vis its content, style, and reception. Despite the increasing number of translations, the challenge of representing Arabic literature in foreign languages still poses several inquiries; How do the cultural and political dynamics of globalization influence the selection of works to be translated? Are there compulsory criteria to meet global preferences? To what degree does translation authentically preserve the identity of the Arab social Reality particularly, works connected to women, religion, and civil conflicts? Hence, the study employs postcolonial theory and cultural translation theory as frameworks to examine the different dynamics controlling the translation process in selected literary works. The paper reveals that translation can strip a text of its cultural background and linguistic nuances in order to internationalize its interpretation. Thus, this paper underscores that translation in the current globalized framework is a double-edged sword; it can function as an instrument for promoting worldwide national understanding or as an apparatus for propagating prejudiced notions. The study, therefore, suggests that Arab translators have to play a more active role in determining which works are to be translated and how they are transferred into other languages.
The Reality of Translating Arabic Literature in the Shadow of the Dominance of Globalized Discourse
intervention
Keywords: Arabic literature; Dynamics; Globalization; Postcolonial theory; Translation; الأدب العربي; الديناميكيات; العولمة; نظرية ما بعد الاستعمار; الترجمة